If $G_1\cong G_2$ and $H_1\cong H_2$ then $G_1 \times H_1 \cong G_2 \times H_2$


$f_G:G_1\rightarrow G_2$ and $f_H:H_1\rightarrow H_2$.

Question 1: Is the following statement valid? Does it belong in this proof?

$$f_G:G_1\times A \rightarrow G_2 \times A\textrm{ for any group }A$$

Question 2: Can I finish the proof like this? Do I need to show any steps in between?

$$\left[\ f_H \circ f_G\right] :G_1\times H_1 \rightarrow G_2 \times H_2$$

$f_G$ and $f_H$ are both bijective. Thus $f_H\circ f_G$ is bijective. Therefore, $G_1 \times H_1 \cong G_2 \times H_2$.

Does this work? I was considering breaking it down further and manipulating individual elements in the groups $G_1,G_2,H_1,H_2.$ I would appreciate your advice. Thanks

  • $\begingroup$ Where does your $f_G$ take an arbitrary element $(g,h)$? $\endgroup$ – Mathmo123 Sep 29 '14 at 19:51
  • $\begingroup$ I suppose $f_G\left[(g_1,h)\right]=(g_2,h)$ where $g_1\in G_1, g_2\in G_2$. Edit: Although maybe I did this improperly--can $f_G$ take a two-element coordinate and simply not change the 2nd element of the coordinate? This assumption is what I based my entire proof on. $\endgroup$ – Patrick Shambayati Sep 29 '14 at 19:54
  • $\begingroup$ @Mathmo123 forgot to tag your username in that last post. $\endgroup$ – Patrick Shambayati Sep 29 '14 at 20:00
  • $\begingroup$ yes it can and in which case your proof works (you still need to verify that that $f_G$ acts as a homomorphism in the way you've constructed it, not just a bijection, but that isn't tricky). The easier way to write it is to let $f$ be the function that takes $(g,h) \mapsto (f_G(g), f_H(h))$ $\endgroup$ – Mathmo123 Sep 29 '14 at 20:08
  • 1
    $\begingroup$ Yes exactly - and then you can use that $f_G$ and $f_H$ are homomorphisms $\endgroup$ – Mathmo123 Sep 29 '14 at 20:23

For the sake of completeness. Take $G_1 \cong G_2,H_1 \cong H_2$ with isomorphisms $f_1,f_2$ respectively. Then take $g((x,y)) = (f_1(x),f_2(y))$.


$g((x_1,y_1)) = g((x_2,y_2)) \implies (f_1(x_1),f_2(y_1)) = (f_1(x_2),f_2(y_2))$

$\implies f_1(x_1) = f_1(x_2) \land f_2(y_1) = f_2(y_2) \implies x_1 = x_2 \land y_1 = y_2$


Take $(x,y) \in G_2 \times H_2$, by surjectivity of $f_1$ there is an $x_1$ such that $f_1(x_1) = x$ and by surjectivity of $f_2$ there is an $x_2$ such that $f_2(x_2) = y$. Thus, $g(x_1,x_2) = (x,y)$


$g((x_1,y_1)(x_2,y_2)) = g(x_1x_2,y_1y_2) = (f_1(x_1x_2),f_2(y_1y_2)) = (f_1(x_1),f_2(y_1))(f_1(x_2),f_2(y_2))$ since $f_1,f_2$ are homomorphisms.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.